Wiara w Kościele, lecz dla świata. Rekonstrukcja interpretacji nauczania Vaticanum II - Andrzej Napiórkowski (Polonia Sacra)
With more and more time perspective, it is easier and more correctly to read the meaning and spirit of the Second Vatican Council (1962–1965). The article shows that it was not dogmatic or even pastoral – as it is often said to be. Its main aim was to develop a new relationship between the Church and the modern era, between Christianity and the essential elements of modern teaching. For popes John XXIII and Paul VI it was not important to conform to the world, but to present and remind modern man – inclined to move away from God – the importance of Gospel’s Truth in all its purity. Therefore Vatican II defined firstly, the relationship between faith and modern teaching, secondly, established the relationship between the Church and the modern state, and finally, differently specified the relationship between Christian faith and religions in the world. Despite many tensions between the socalled “traditionalists” and “progressives”, the Council was ultimately a brilliant event of the Holy Spirit and human effort, renewing the face of the Church and the hearts of Christians especially in the modern perspective of faith. The Council opened the Church for people thanks to the call of enlarging the faith in Jesus Christ.